Performance comparison of distributed generation installation arrangement in transmission system for loss control - S. A. S.; I. Musirin; S. I. Sulaiman; M. H. Mansor; S. A. Syed Mustaffa (Bulletin of Electrical Engineering and Informatics, 2019)
Placing Distributed Generation (DG) into a power network should be planned wisely. In this paper, the comparison of having different installation arrangement of real-power DGs in transmission system for loss control is presented. Immune-brainstorm-evolutionary programme (IBSEP) was chosen as the optimization technique. It is found that optimizing fixed-size DGs locations gives the highest loss reduction percentage. Apart from that, scattered small-sized DGs throughout a network minimizes transmission loss more than allocating one biger-sized DG at a location.